An Investigation On Character Strengths Of Adolescents In Penang And Kedah - Cheng, Chiau Chui (2020)
Character strengths have been found to be significantly associated with adolescents’ well-being and flourishing. Meanwhile, parent-child relationship and teacher-student relationship plays an important role in building character strengths of adolescents. The present study examined character strengths and flourishing among adolescents in Penang and Kedah. It also investigated parent-child relationship and teacher-student relationship and how character strengths contribute to flourishing of the adolescents in Penang and Kedah. Participants in the current study included a total of 217 secondary school’s students from three schools located in Northern states of Malaysia. Mixed methods were applied, with a quantitative and a qualitative study. Using survey, Study 1 focused on the character strengths, parent-child relationship, teacher-student relationship and flourishing in a sample of 117 students. Results revealed that kindness was ranked as the top character strength, and leadership was ranked as lowest strength among the adolescent. The parent-child relationship reported by adolescence was high in control and low in care while teacher-students relationship reported by the sample in this study was high in quality. Numerous character strengths were positively correlated with parental care, parental control and relationship with teachers. Perseverance and judgement agency were significant predictors of flourishing. Study 2 used a series of open-ended questions to examine character strengths, parent-child relationship, teacher-student relationship and flourishing among 100 participants.